Professional Ethics, Provenance, and Policies: A Survey of Dead Sea Scrolls Scholars - Bonnie, Rick (Dead Sea discoveries, 2020)
This article presents and discusses the results of an online survey undertaken in 2018, which targeted scholars of the Dead Sea Scrolls and associated research fields. Respondents were asked questions on the state of knowledge in the field regarding provenance issues and related ethics and policies. The goal of the survey was to establish the levels of awareness within Qumran and related studies concerning the role of the antiquities market, the potential accountability (or not) of scholars as perceived by respondents, as well as their general awareness of relevant policies and codes of conduct. The article discusses the key points that the survey raised, with the aim of offering textual scholars tools to assess their role in provenance issues.